The Effect of Geogebra Learning Media on Spatial Capability and Understanding of Students' Mathematics Learning Concepts - Hidayat, Nurul; Abidin, Zainal; Setiawan, Yayan Eryk (JME (Journal of Mathematics Education), 2024)
The purpose of this study was to see how geometry learning media on flat-sided geometrical material affected the spatial abilities and understanding of learning ideas in Probolinggo Private MTs class 8 pupils. The experimental research approach was given to courses VIII-B and VIII-C. The control class is VIII-B, and the experimental class is VIII-C. Class VIII-B has 30 students, while Class VIII-C has 25. Pre-test, post-test, and questionnaire data-gathering approaches are used. Pre- and post-tests were used to examine the influence of geometry on students' knowledge of learning concepts, while surveys were used to determine the effect of geometry on students' psychological capacities. The data was analyzed using the Z-test. The findings of the study reveal that: (1) Geogebra learning media on flat-sided geometric material influence students' spatial ability. (2) Students' knowledge of learning ideas is improved when Geogebra learning media are used in class functional content compared to students who do not use Geogebra.